FAKTOR PENENTU KUALITAS AUDIT DI KANTOR AKUNTAN PUBLIK DKI JAKARTA - Momon Momon; Widarto Rachbini; Amilin Amilin (STIE Muhammadiyah Jakarta, 2020)
The study aims to analyze the effect of auditor competence and independence on audit quality. The sample used in this study were 151 samples (KAP) represented by the Auditor in DKI Jakarta. Data analysis uses descriptive and inferential analysis using multiple regression analysis. Hypothesis testing results indicate that there is a significant positive effect on Auditor Competence and Auditor Independence on Audit Quality. These results indicate that the higher (both) Auditor Competency and Auditor Independence, the Audit Quality will increase. Independent auditors should pay attention to their competencies. To improve audit quality, it is necessary to increase the competence of auditors by providing training and certification of expertise that supports the auditor profession in line with continuing professional education (PPL) programs. The role of regulators and accountants' associations (IAPI, IAI) in this case is also very necessary to monitor the implementation of the PPL program for auditors (accountants). Auditors who conduct audits must truly maintain and ensure independence both in fact and in appearance in order to produce quality audits. The existence of regulations that limit the length of the audit of a client conducted by the same public accountant, should also be supported by the KAP to rotate the auditor team, not only limited to the level of partners signing the audit report to further maintain its independence.